How Nurse Job Satisfaction is Affected by Compensation, Work Motivation, and Work Environment - Sultan Sultan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The main goal of this study is to find out how salary, work motivation, and the work surroundings affect how happy nurses are with their jobs in the inpatient ward of Jayapura Hospital. Questionnaires and interviews with 186 nurses at Jayapura Hospital were used to collect raw data for this study. The story says that the hospital has 350 nurses in total. The people who did this work used the statistical programme SPSS version 23 to do quantitative analyses, such as multiple linear regression analysis and coefficient of determination analysis. We found that pay and work environment have a statistically significant and positive effect on nurse job happiness in the inpatient ward of Jayapura Hospital. This was shown by the T-test and F-test results. Despite this, it was found that work motivation does not have a statistically significant effect on job happiness in this group of nurses. Within the walls of Jayapura Hospital, study has shown that pay, work motivation, and the work environment all have a statistically significant and positive effect on how satisfied inpatient room nurses are with their jobs. After looking at the coefficient of determination, we can say that pay, work motivation, and the work environment all together account for 21.7% of the differences seen in nurse job happiness. Eighty-seven percent of the conflict is still being resolved because of outside factors that were not included in this study.